C-Reactive Protein Levels Predict Outcomes in Continuous-Flow Left Ventricular Assist Device Patients: An INTERMACS Analysis. Issue 8 (August 2021) - Batra, Jaya; Truby, Lauren K.; Defilippis, Ersilia M.; Takeda, Koji; Takayama, Hiroo; Naka, Yoshifumi; Yuzefpolskaya, Melana; Colombo, Paolo C.; Sayer, Gabriel; Farr, Maryjane A.; Garan, A. Reshad; Uriel, Nir; et al.
Abstract : CRP is an established inflammatory biomarker with prognostic value in patients with chronic heart failure, yet its role in continuous-flow left ventricular assist device (LVAD) patients is largely unknown. 5, 183 patients from the INTERMACS registry who underwent durable LVAD between 2008 and 2017 and had preimplant CRP levels were included. The sample was stratified into two groups based on preimplant CRP levels: CRP of 0–10 mg/L (low) and >10 mg/L (high). Kaplan-Meier survival estimates were used to assess outcomes at 2 years after LVAD implantation, with log-rank testing used to compare groups. Cox proportional hazard models were used for multivariable adjustment. Patients with high preimplant CRP were younger, more likely to be INTERMACS class I, and had a higher need for temporary mechanical circulatory support before LVAD implant compared to those with lower CRP levels (all P < 0.001). The high CRP group had higher WBC counts and BNP levels (all P < 0.001). After adjustment, higher CRP (>10 mg/L) was associated with greater risk of mortality, RV failure, and stroke postimplant ( P < 0.001). In addition, elevated postimplant CRP level at 3 months was associated with increased mortality and stroke on LVAD support ( P < 0.001). CRP is a predictor of death and complications on LVAD support. Future studies are necessary to explore the mechanisms underlying this finding and the potential role of antiinflammatory therapies in this population. Abstract : Supplemental Digital Content is available in the text.